Reviews of recent publications - various authors (Studies in 20th & 21st Century Literature, 1991)
Cary Nelson and Lawrence Grossberg, eds., Marxism and the Interpretation of Culture, by John Barberet Asunción Horno-Delgado, Eliana Ortega, Nina M. Scott, and Nancy Saporta Sternbach, eds., Breaking Boundaries: Latina Writing and Critical Readings, by Amy Kaminsky Jonathan Culler, Framing the Sign: Criticism and Its Institutions, by Rosemarie Scullion Wolfgang Iser, Prospecting: From Reader Response to Literary Anthropology, by Jane Riles Thomas Colin Davis, Michel Tournier: Philosophy and Fiction, by Marja Warehine Didier Coste, Narrative as Communication, by Armine Kotin Mortimer Jean-Jacques Thomas, La Langue, la poésie. Essais sur la poésie française contemporaine, by Thomas F. Broden Manfred Dierks, Adolf Muschg, by Judith Ricker Guy Stern, Literatur im Exil. Gesammelte Aufsätze 1959-1989, by Wulf Koepke
Keywords: Cary Nelson; Lawrence Grossberg; Marxism and the Interpretation of Culture; Asunción Horno-Delgado; Eliana Ortega; Nina M. Scott; Nancy Saporta Sternbach; Breaking Boundaries: Latina Writing and Critical Readings; Jonathan Culler; Framing the Sign: Criticism and Its Institutions; Wolfgang Iser; Prospecting: From Reader Response to Literary Anthropology; Colin Davis; Michel Tournier: Philosophy and Fiction; Didier Coste; Narrative as Communication; Jean-Jacques Thomas; La Langue; la poésie. Essais sur la poésie française contemporaine; Manfred Dierks; Adolf Muschg; Guy Stern; Literatur im Exil. Gesammelte Aufsätze 1959-1989; John Barberet; Amy Kaminsky; Rosemarie Scullion; Jane Riles Thomas; Marja Warehine; Armine Kotin Mortimer; Thomas F. Broden; Judith Ricker; Wulf Koepke